Pengembangan Website dan Kerjasama Katering Bungli Coffeeshop di Batam - Fahlevi, Renza; Giorgyna, Giorgyna (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2025)
Founded by Mrs. Bungli in 2010 in Batam City, Bungli Coffeeshop has emerged as a leading culinary destination offering a diverse range of services, including catering, birthday events, celebrations, and social activities. Renowned for its signature dishes such as seasoned chicken and mixed rice with a variety of side dishes, Bungli Coffeeshop has crafted a distinctive culinary experience that captivates consumers. This study aims to propel the progress of Bungli Coffeeshop by introducing innovation through the establishment of a website and the development of a catering collaboration proposal. With a focus on employing interview, observation, and documentation methods, this research aims to support Bungli Coffeeshop in entering a new phase of business development. The results of this research indicate a significant improvement in the business performance of Bungli Coffeeshop. Through the establishment of a website, the business has successfully gained broader exposure, attracting new customers and providing a better experience for loyal patrons. Furthermore, the formulation of a catering collaboration proposal expands opportunities for business partnerships, opening doors to mutually beneficial collaborations. This study provides a deeper understanding of the importance of innovation in the culinary business world and offers practical guidance for planning the next steps in the development of Bungli Coffeeshop. With these efforts, it is anticipated that Bungli Coffeeshop will continue to grow and become a key player in the culinary industry in Batam City and its surroundings. Keywords: Digital marketing, bungli coffeeshop, catering, dish, restaurant